Penggunaan Modul IPA STEM terintegrasi Crosscutting Concepts pada Rasa Ingin Tahu Peserta Didik SMP - Fairuz Zakirah; Asri Widowati (Postgraduate, University of Mataram, 2024)
One of the goals of learning science is to help students develop their science curiosity. Students' curiosity is a personality trait motivated by the desire to find a solution or fill a specific knowledge gap. Using science modules in science is expected to be a solution to stimulate student’s science curiosity. The purpose of this study was to determine the curiosity level of class VII students at SMP Negeri 1 Yogyakarta, especially on the temperature and heat topic. Type of this research is descriptive qualitative. Data analysis used the N-gain test to determine the increase in student’s science curiosity. The subjects in this study were students of class VII G SMP Negeri 1 Yogyakarta, who collected 32 students using purposive sampling technique. Data collection techniques consist of questionnaires and the data collection used in the form of pretest and posttest. Based on the data analysis there is difference in the pretest and posttest results with the average N-gain obtained is 0.69, which is in the medium category. It can be concluded that the use of STEM integrated Crosscutting Concepts can improve students’ science curiosity. This is evidenced by the difference in pretest and posttest, also the N-gain score which is in medium category.